Achieving Sustainable Coastal–marine Conservation: Lessons from a Community Social Movement in Torosiaje Ecotourism Village, Indonesia - Hendra, Hendra; Sumarmi, Sumarmi; Astina, I Komang; Aisyah, Siti; Rijal S, Ahmad Syamsu (Three E Science Institute, 2025)
The failure of top-down conservation in natural resource management continues to provoke resistance led by local communities. This study analyzes how the coastal community of Torosiaje constructs a polycentric governance system through collective action in response to ecological crises and to the state's appropriation of living space, aiming to achieve blue justice in the management of marine and coastal resources. The complex, polycentric governance in joint management involves various actors, including the state, local communities, and the private sector, who collectively play active roles in decision-making for sustainability. Meanwhile, blue justice requires the fair distribution of natural resources and ecosystem benefits, which is pursued through the collective struggle of the community against ecological injustice. Using social movement and political ecology theories as an analytical framework, this research redefines Community-Based Natural Resource Management (CBNRM) as a more inclusive and responsive model to local dynamics. A qualitative case study design was employed through in-depth interviews, participant observation, and document analysis, which were subsequently analyzed thematically. The findings reveal that integrating local knowledge and formal rules, embodied in the paddakuang and sipakullong conservation groups, results in a more adaptive and just CBNRM model in response to resistance. Cross-village collaboration, participatory ecotourism, and culture-based education strengthen the socio-ecological dimensions of this polycentric governance. This study contributes theoretically by applying social movement theory to redefine successful CBNRM. It argues that sustainable governance is a political outcome shaped by community resistance to ecological injustice and state dispossession, rather than merely a technical model.